Rozprawy Wiesława Kozuba-Ciembroniewicza w "Studiach nad Faszyzmem i Zbrodniami Hitlerowskimi" - Maciejewski, Marek; Scheffler, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Professor Wiesław Kozub-Ciembroniewicz was one of the most often published authors in the journal Studies on Fascism and Nazi Crimes. Undoubtedly, it was related to the fact that the issues raised by him were new or relatively little known in Polish scholarly thought. The research effort of this Cracow scholar has left a clear mark not only on his direct pupils and successors but also on the vast circle of Polish researchers, especially those with doctrinal and historical-legal inclinations. The Authors believe that the scientific legacy of Professor Kozub-Ciembroniewicz will continue to be an inspiration for successive generations of lawyers, political scientists and historians for many years.
Keywords: totalitarianism; fascism; National Socialism; Kozub-Ciembroniewicz, Wiesław